SIFAT-FK RUANG BARISAN CESARO ORLICZ - Haryadi, Haryadi - (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2024)
The Cesaro sequence space , ( , which is the FK-space, has been generalized to the Cesaro-Orlicz sequence space . This prompted the study of several properties in that have been known in . In this paper, the properties of completeness and FK-properties in the Cesaro-Orlicz space are discussed. For this discussion, a modular approach is used. The results of the study show that the space is a convex modular space. This sequence space is also complete to the Luxemburg norm and has K-properties. Furthermore, this space is a BK-space. These results can be used to study the Kothe-Toeplitz dual, which is an important part of the transformation of the infinite matrix